Lipopolyplex for Therapeutic Gene Delivery and Its Application for the Treatment of Parkinson’s Disease - Chen, Wei; Li, Hui; Liu, Zhenguo; Yuan, Weien (Frontiers in Aging Neuroscience, 2016)
Abstract: Lipopolyplex is a core-shell structure composed of nucleic acid, polycation and lipid. As a non-viral gene delivery vector, lipopolyplex combining the advantages of polyplex and lipoplex has shown superior colloidal stability, reduced cytotoxicity, extremely high gene transfection efficiency. Following intravenous administration, there are many strategies based on lipopolyplex to overcome the complex biological barriers in systemic gene delivery including condensation of nucleic acids into nanoparticles, long circulation, cell targeting, endosomal escape, release to cytoplasm and entry into cell nucleus. Parkinson’s disease is the second most common neurodegenerative disorder and severely influences the patients’ life quality. Current gene therapy clinical trials for Parkinson’s disease employing viral vectors didn’t achieve satisfactory efficacy. However, lipopolyplex may become a promising alternative approach owing to its stability in blood, ability to cross the blood-brain barrier and specific targeting to diseased brain cells.